Economic dispatch problem considering natural gas system / Muhamad Ridzuan Mamat - Mamat, Muhamad Ridzuan (2014)
In recent years, electricity generation using natural gas has been increased by considering the electric network and natural gas system as a single energy system, the economic operation of the system can be determined. This paper presents a solution to economic dispatch problem by considering the natural gas system. This solution is developed based on lambda iteration method. The approach is tested on a three unit generation systems. The results show that the economic dispatch solution can be obtained by integrating the natural gas system.